Effects of subjective stress levels on learning effectiveness in high-fidelity simulation among healthcare workers - Suh, Yoong-A; Shim, Hoyeon; Lee, Hae Jeong; Lee, Jang Hoon; Park, Moon Sung; Choi, Seoheui (Acta psychologica, 2025)
Appropriate stress reportedly influences memory gains. However, stress levels may vary across individuals and may lead to changes in vital signs as a physiological response induced by endogenous hormone secretion. The aim of this study was to evaluate the impact of high-fidelity simulation (HFS) training on cognitive performance using Perceived Stress Scale (PSS) scores as a subjective stress indicator and vital sign measurements as an objective stress indicator during Neonatal Resuscitation Program training. This study was conducted as a single-blind randomized controlled study with a pre–post design for health care workers, including paediatric residents and nurses in charge of neonatal care. The trainees' vital signs and PSS scores were measured and determined before, during, and after each training session, and the results were analysed. A comparison of vital signs between groups after each training session revealed significant changes in heart rate (HR), and the PSS score significantly increased after practical training (2nd HR; 78.4 ± 9.0 vs. 87.7 ± 8.7, p = 0.05; 3rd HR 83.1 ± 9.0 vs. 76.7 ± 8.1, p = 0.041: 2nd PSS 15.1 ± 3.3 vs. 18.2 ± 4.8, p = 0.040), but there was no difference between the groups in terms of the final confirmed test result or PSS score (3rd result 66.3 ± 24.4 vs. 72.7 ± 12.7, p = 0.360; 3rd PSS 17.2 ± 4.9 vs. 16.1 ± 4.8, p = 0.510). When comparing vital signs, test scores, and PSS scores before and after HFS, regardless of the training sequence, no statistically significant changes were observed in the HR or respiratory rate (RR). However, body temperature (BT; 36.5 ± 0.3 vs. 36.7 ± 0.3, p < 0.001), mean blood pressure (BP; 81.9 ± 11.8 vs. 84.8 ± 10.2, p = 0.030), test scores (51.0 ± 26.2 vs. 56.6 ± 23.2, p < 0.001), and PSS scores (15.8 ± 3.8 vs. 17.7 ± 4.8, p = 0.036) significantly increased, whereas SpO2 significantly decreased (99.3 ± 0.8 vs. 98.8 ± 1.4, p = 0.017). Multiple regression analysis was conducted to assess the relationship between PSS variability and final test score improvements. This revealed a significant relationship, as described by the following equation: final score difference = 34.997 + 1.637 × PSS variability (p = 0.006). The results of the analysis revealed a statistically significant relationship between the variability in subjective stress levels (PSS variability) and the improvement in final scores. This finding suggests that the greater the variability of subjective stress levels is, the greater the improvement in final scores is. Further research is needed to explore these relationships across different populations and training scenarios. •This study examined how stress, measured by vitals and PSS scores, affects cognition during simulation training.•This study revealed a significant relationship between subjective stress variability and training outcomes.•Moderate stress levels were found to enhance memory consolidation during healthcare simulation training.